WETU TELU; Suatu Bentuk Keberagaman Pendidikan Pembebasan Berbudaya Masyarakat Lombok - Saladin, Bustami (STAIN PAMEKASAN, 2012)
AbstractOn each occasion many cultural experts, observers of culture and cultural practitioners feel a great concern to the culture of the past who have started eroded by foreign cultures is not a country boy culture. Concerns can be seen from at least the younger generation who still recognize and remember the ancestors of its culture that are considered modern and outdated At this time the traditional culture which is a tradition of delivering the message has long been used long before humans knew the writing, community advocates maintain that tradition this ceremony as a tradition that has been